Saying the unsaid from the said : a critical discourse analysis of President Buhari’s five minutes broadcast after his 105 days medical vacation in London - Yekeen, Bello; Oyeniyi, Adeniyi-Egbeola Folakemi; Rabiat, Fakunle Oiza (Penerbit Universiti Kebangsaan Malaysia, 2022)
The paper explores President Muhammadu Buhari of Nigeria use of language in political setting. As a President, his choice of words and the language use speak a lot. Being a formal Military leader, his broadcast was more ‘khakitocratic’ (military) than democratic. His speech lasted five minutes but assessed using critical discourse analysis (CDA). The paper discusses context and culture in discursive interactions. Political language democratically, is important to national unity as it can illicit positive or otherwise reactions from electorates. Analysis for the study was based on Fairclough’s three dimensional conceptualisation of discourse with the aid of tabular illustrations. Findings reveal assumptions that unsaid words have implicit meanings than the said, being that words are neutral and, of course, the unsaid ideological politics of meanings could establish ‘khakitocratic’ language through discourse. The study concludes that people need ontological and epistemological inferences to develop societal consciousness about socio-political engagements to enhance understanding of undefined expressions.